2017
DOI: 10.4236/arsci.2017.53004
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Caesarean Section among Pregnant Women in a Rural Missionary Hospital

Abstract: Introduction: Caesarean section is the delivery of a foetus through an incision made on the uterus. It is useful in situations where vaginal delivery is not feasible. Women in our setting usually see it as a reproductive failure and a sign of weakness. Our aim was to evaluate the perception of caesarean section among pregnant women attending antenatal clinic in a rural missionary hospital. Methodology: This was a cross-sectional study conducted at Mile 4 missionary hospital, Abakaliki among women attending rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In the study conducted at Abakaliki, Nigeria among women attending routine antenatal clinic, fear of death was the major reason women refused caesarean section. 1 This was not seen in this study, as the women in this study had better access to information and education, as compared to their Nigerian counterparts.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In the study conducted at Abakaliki, Nigeria among women attending routine antenatal clinic, fear of death was the major reason women refused caesarean section. 1 This was not seen in this study, as the women in this study had better access to information and education, as compared to their Nigerian counterparts.…”
Section: Discussionmentioning
confidence: 63%
“…Caesarean section is an alternative for women when a vaginal delivery is not possible. 1 The indications for a caesarean section could be maternal or foetal. It is a relatively safe surgical procedure, though there may be some associated complications.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, there have been reports from many countries especially West African countries where mothers have said they would refuse to undergo a CS even when medically indicated [34][35][36][37]. Informed refusals especially when the fetus's life is at risk is challenging.…”
Section: Aversion Towards Csmentioning
confidence: 99%
“…One Nigerian study (n=413) reported of mothers (12%) unwilling to accept the procedure under any circumstance [36]. Reports of refusals are mostly from low income countries [34,35,38], but a small proportion are also reported from high income countries [37].…”
Section: Aversion Towards Csmentioning
confidence: 99%
See 1 more Smart Citation